2006
DOI: 10.1164/rccm.200507-1123oc
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Markers of Inflammation and Coagulation in Patients with Coronary Heart Disease

Abstract: These results suggest that inflammation as well as parts of the coagulation pathway may contribute to the association between particulate air pollution and coronary events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
278
2
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 361 publications
(315 citation statements)
references
References 47 publications
32
278
2
3
Order By: Relevance
“…Medication use in asthmatics also increased in association with the cumulative exposure to UFP over 5 or even 14 days (von Klot et al, 2002). Ru¨ckerl et al (2006) observe the highest increases in some blood markers in patients with coronary heart disease at a lag of 48 to 71 h. However, other studies observed immediate associations of UFP on mortality or morbidity, respectively (Forastiere et al, 2005;von Klot et al, 2005).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Medication use in asthmatics also increased in association with the cumulative exposure to UFP over 5 or even 14 days (von Klot et al, 2002). Ru¨ckerl et al (2006) observe the highest increases in some blood markers in patients with coronary heart disease at a lag of 48 to 71 h. However, other studies observed immediate associations of UFP on mortality or morbidity, respectively (Forastiere et al, 2005;von Klot et al, 2005).…”
Section: Discussionmentioning
confidence: 79%
“…Recently, adverse health effects were reported for elevated particle number concentrations (NC) in the ultrafine range Ibald-Mulli et al, 2002) including a decrease in peak expiratory flow (PEF) (Pekkanen et al, 1997;Peters et al, 1997b;Penttinen et al, 2001), increases in medication use of asthmatics (von Klot et al, 2002), increases in blood markers (Ru¨ckerl et al, 2006), repolarization changes in ischemic heart disease patients (Henneberger et al, 2005), increased hospital cardiac readmissions in myocardial infarction survivors (von Klot et al, 2005) and an increase in out-of-hospital coronary deaths (Forastiere et al, 2005). Associations of mortality with UFPs have been reported to be of approximately the same magnitude per interquartile range as with PM 2.5 but independent of the PM 2.5 associations in a 3-year study , reanalyzed by Sto¨lzel et al, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis of increased coagulability due to PM [4] is supported by epidemiologic evidence in both general and particularly susceptible populations [5,6]. However, a DE-specific healthy animal model showed decreased plasminogen activator inhibitor-1 (PAI-1), implying increased thrombolysis, in response to DE [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some epidemiological studies have shown adverse health effects associated with exposure to the ultrafine particulate fraction of air pollution [Peters et al 1997[Peters et al , 2004Penttinen et al 2001;Ibald-Mulli et al 2002;Timonen et al 2004;Ruckerl et al 2006] although uncertainty exists about the role of ultrafine particles relative to other air pollutants in causing the observed adverse health effects. The associations in these studies have been based on measurements of the particle number or mass concentrations of particles within certain size fractions (e.g., particulate matter with diameter of 2.5 µm and smaller [PM 2.5 ]).…”
Section: Observations From Epidemiological Studies Involving Fine Andmentioning
confidence: 99%